PERANAN AKUNTAN PUBLIK DAN STANDAR AKUNTANSI KEUANGAN ATAS AKTIVITAS REKSA DANA - Viona Wijaya (Center for Economic Studies Universitas Katolik Parahyangan, 2007)
Potencies and characteristics of Mutual Fund in the future will be expanded. Data and statistic about mutual fund has shown increase rate. It will always continue with economical development, and especially in capital market development. So, public-accounting's role for mutual funds activities will increase, and Financial Accounting Standard which related to mutual fund will be very important to understand.